Match demands of beach soccer: A case study - Scarfone, R.; Tessitore, A.; Minganti, C.; Ferragina, A.; Capranica, L.; Ammendolia, A. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Despite the increasing worldwide popularity of Beach Soccer, played either at amateur and professional level, few scientific studies focused on this sport, leaving open several questions about its performance profile. Thus, the aim of this study was to examine the responses to a Beach Soccer friendly match in varsity players. Methods Ten male players (age 23.6±4.4 yrs; body mass 71.8±3.8 kg; height 1.77±0.05m) of the Magna Græcia University beach soccer team provided their written consent to participate in the study. The subjects were divided in two teams (1 goalkeeper, 2 defenders, 1 pivot, and 1 attacker). The beach soccer match consisted of three 12-min periods with 3-min breaks in between. During the match heart rate was continuously recorded every 5 s (Polar Team System, Polar Electro, Finland). Before the match and at the end of each period blood lactate concentrations (La; Accusport, Roche, Switzerland) and power performances (countermovement jump, CMJ; Optojump, Microgate, Italy) were measured. To estimate the intensity of efforts during the match, HR was expressed as a percentage of HRmax using 5 categories: >95%, 86-95%, 76-85%, 65-75%, <65%. ANOVA for repeated measures was used to test differences (p<0.05) between periods. Results Match intensity showed differences for HR categories (p=0.001) and their interaction with match periods (F(8, 64)= 4.18; p=0.0005), and La values (p=0.03). A progressive decrease of occurrence toward the end of the match emerged for HR>85% (periods: first=75%, second=61%, third=31%). A similar trend emerged for La values (periods: first=8.7±4.0mmol.L-1; second=6.7±3.8mmol.L-1; third=5.3±2.7mmol.L-1). With respect to pre-match condition (36.6±5.3cm), higher (p<0.004) CMJ performances were found at the end of the match periods (first=39.5±6.5cm; second=40.9±6.4cm; third=39.2±6.0cm). Discussion The present findings indicate that Beach Soccer is an intermittent sport activity that places a high load on players, with the anaerobic metabolism providing an important energy source during games. Although the marked decrease in intensity of playing might indicate that players undergo fatigue (Mohr et al., 2003), this speculation is in contrast to the increased CMJ performances of players, which might be attributed to an enhanced neuromuscular activation (Vetter, 2007). Thus, it might be hypothesized that players tend to adopt tactical strategies to spare their energies throughout the match and further studies are necessary to clarify these aspects.